(untitled) (Advances in Applied Biological Research, 2025)
Background: Plants are used as complementary and alternative medicine for a variety of conditions, regardless of their crude or as their separated pharmacological components. The purpose of this study was to assess in vitro antioxidant and in vivo cardio protective of the Phyllanthus maderaspatensis. Methodology: Quantitative analysis and Gas Chromatography-Mass Spectrometry (GC-MS) phytochemical study based on solvent method of extraction were carried out. Using the conventional method of antioxidant assay among the leaf extract were ascertained. Isoproterenol (ISO)-treated rats were used for in vivo experiment to check the effect of plant extract on cardio protective bio markers. Results. There is an increased total antioxidant activity of extract found in a dose-dependent manner. At 50 μg, 19-24% activity and at 400 μg, 79-84% scavenging potential was recorded. The rats receiving the extract showed a decrease in heart weight and an increase in body weight. The mean concentration of cardiac troponin (cTn) T/I in the serum of rats treated with the standard drug reduced effectively (1.13±0.07/0.64±0.05 ng/mL), whereas significantly by the extract (1.25±0.19/0.72±0.08 ng/mL). The creatine kinase MB (CKMB) of the standard was significant at 78.33±6.26IU, and the extract was 83.35±7.51IU. The data showed increased values among the standard and extract compared to the control group but were found to be significantly (p < 0.001) decreased among the treated groups. Compared to negative control animals (healthy rats), isoproterenol (ISO)-treated rats had significantly increased levels of aspartate myocardial cell damage. After 5 weeks of treatment, in comparison to those in the positive control (PC), extract-treated rats had significantly (p <0.05) elevated levels of serum AST, alanine transaminase (ALT), alkaline phosphatase (ALP), and lactate dehydrogenase (LDH). Recovery from ISO-induced electrophysiological abnormalities was confirmed by decreased serum cardioprotective markers, mainly troponin and CKMB. The damage to the heart tissues was significantly reduced and found closer to control and standard drug-treated groups at doses of 200 mg/kg body weight (bwt). The data confirm that the cardioprotective benefits are attributed to the presence of antioxidant components in the extract of Phyllanthus maderaspatensis.